Estoques de carbono resultantes de mudanças de uso e cobertura do solo e sua relação com os indicadores socioeconômicos nos municípios de Paragominas e Ulianópolis, Pará - SOUSA, Larissa Melo de (Universidade Federal do Pará, 2019)
The land use land cover change are pointed out by several studies to cause environmental damage, such as carbon dioxide (CO2) into the atmosphere The objective of this study is to relate the socio-economic indicators and carbon emissions with the different land use land cover change in the municipalities of Paragominas and Ulianópolis for the years 2004, 2008, 2010 and 2012. For this, they were certain areas according to each class of use and land cover and the mean of the stock of Above Ground Biomass (AGB) for each of the classes of use and land cover provided by TerraClass Project for 2004. Subsequently were quantified CO2 emissions associated with land use land cover change cover. In addition, the socioeconomic data were related to estimates of carbon. The results indicate that much of the forest area was converted to the classes of agriculture and pasture. The total carbon stored above ground, between the period 2004 to 2012 ranged from 163 x106 Mg C to 161 x106 Mg C Mg C in Paragominas and de 31 x106 Mg C to 29 x106 Mg C in Ulianópolis. The net CO2 emissions between the period 2004 to 2012 amounted to 5.8x106 Mg CO2 to Paragominas and 7.4 x106 Mg CO2 to Ulianópolis. In Ulianópolis it was observed a moderete linear relationship between socioeconomic indicators and carbon stocks, while in Paragominas, there was no linear correlation. The conclusion is that the dynamics of use and land cover classes are based on agriculture and livestock as variables in the economic matrix of the municipalities. The carbon stock in the municipalities has decreased due to reduction of forest areas and the advancement of areas of annual agriculture and clean pasture, so the study area is negatively contributing to the removal of CO2 from the atmosphere. Land use land cover change has positive effects on the socio-economic indicators, but increase carbon emissions.